Bi2Te3 nanowire array preparation and surface polishing by electrochemical deposition. (May 2015) - Ren, D.; Guo, T.; Yang, Z.; Mu, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The quantum confinement effect and phonon scattering in low dimensional nanostructure is effective in the improvement of the efficiency of thermoelectric generators. Bi2Te3 nanowire arrays were prepared in Al2O3 templates through the use of electrochemical deposition. Chemical mechanical planarisation was employed to level the upper and lower surfaces of Bi2Te3 samples. The XRD (X-ray Diffractometer) test showed that the crystal grain of Bi2Te3 nanowire was 20–30 nm, attaining a size where the structural properties of the structure induced the quantum confinement effect. It was also indicated that there were dense structures in the fabricated nanowires, the nanowire ends kept at the same level as the hole's edge, solving the problem for the following assembly of thermoelectric transducers. Based on the procedures presented in this paper, there is promise in the future enhancement of the Seebeck coefficient of this nanowire array by introducing nanodoping to the structure.